Multiple Giant Liver Cysts in a Nepalese Lad - Ashish Lal Shrestha; Shova Banstola Paudel; Saurav Krishna Malla (Case Reports in Pediatrics)
Background. While evaluating a child with multicystic liver pathology, both the congenital and acquired etiologies need to be considered. While typicality of findings on abdominal imaging makes the diagnosis of cystic echinococcosis relatively easy, choosing the appropriate line of management is equally crucial. Case Presentation. An 8-year-old previously healthy lad presented to the office with progressive upper abdominal fullness and pain for a year. Blood workup was normal. CT imaging made a diagnosis of multicystic giant hepatic hydatidosis. Treatment consisting of oral albendazole combined with surgical excision resulted in a fruitful outcome. To the best of our knowledge, this probably represents the first case of multiple giant hepatic hydatidosis at such a young age being reported from Nepal. Conclusion. Childhood liver cysts are uncommon. Considering the endemicity, echinococcal etiology needs consideration. Surgical ablation is required for large cysts, and the mode of management is dictated by the size and location.